Analysis of the bacteriorhodopsin-producing haloarchaea reveals a core community that is stable over time in the salt crystallizers of Eilat, Israel - Nikhil Ram-Mohan; Aharon Oren; R. Thane Papke (Extremophiles, 2016)

Greater carbon allocation to mycorrhizal fungi reduces tree nitrogen uptake in a boreal forest - Niles J. Hasselquist; Daniel B. Metcalfe; Erich Inselsbacher; Zsofia Stangl; Ram Oren; Torgny Näsholm; Peter Högberg (Ecology, 2016)
The central role that ectomycorrhizal ( EM ) symbioses play in the structure and function of boreal forests pivots around the common assumption that carbon (C) and nitrogen (N) are exchanged at rates favorable for plant growth. However, this may not always be the case. It has been hypothesized that the benefits mycorrhizal fungi convey to their host plants strongly depends upon the availability of C and N, both of which are rapidly changing as a result of intensified human land use and climate change. Using large‐scale shading and N addition treatments, we assessed the independent and interactive effects of changes in C and N supply on the transfer of N in intact EM associations with ~15 yr. old Scots pine trees. To assess the dynamics of N transfer in EM symbioses, we added trace amounts of highly enriched 15 NO 3 ‐ label to the EM ‐dominated mor‐layer and followed the fate of the 15 N label in tree foliage, fungal chitin on EM root tips, and EM sporocarps. Despite no change in leaf biomass, shading resulted in reduced tree C uptake, ca . 40% lower fungal biomass on EM root tips, and greater 15 N label in tree foliage compared to unshaded control plots, where more 15 N label was found in fungal biomass on EM colonized root tips. Short‐term addition of N shifted the incorporation of 15 N label from EM fungi to tree foliage, despite no significant changes in below‐ground tree C allocation to EM fungi. Contrary to the common assumption that C and N are exchanged at rates favorable for plant growth, our results show for the first time that under N‐limited conditions greater C allocation to EM fungi in the field results in reduced, not increased, N transfer to host trees. Moreover, given the ubiquitous nature of mycorrhizal symbioses, our results stress the need to incorporate mycorrhizal dynamics into process‐based ecosystem models to better predict forest C and N cycles in light of global climate change.

Response to CO 2 enrichment of understory vegetation in the shade of forests - Dohyoung Kim; Ram Oren; Song S. Qian (Global Change Biology, 2016)
Responses of forest ecosystems to increased atmospheric CO 2 concentration have been studied in few free‐air CO 2 enrichment ( FACE ) experiments during last two decades. Most studies focused principally on the overstory trees with little attention given to understory vegetation. Despite its small contribution to total productivity of an ecosystem, understory vegetation plays an important role in predicting successional dynamics and future plant community composition. Thus, the response of understory vegetation in Pinus taeda plantation at the Duke Forest FACE site after 15–17 years of exposure to elevated CO 2 , 6–13 of which with nitrogen (N) amendment, was examined. Aboveground biomass and density of the understory decreased across all treatments with increasing overstory leaf area index ( LAI ). However, the CO 2 and N treatments had no effect on aboveground biomass, tree density, community composition, and the fraction of shade‐tolerant species. The increases of overstory LAI (~28%) under elevated CO 2 resulted in a reduction of light available to the understory (~18%) sufficient to nullify the expected growth‐enhancing effect of elevated CO 2 on understory vegetation.